2017
DOI: 10.1002/chem.201705306
|View full text |Cite
|
Sign up to set email alerts
|

Diastereomeric Right‐ and Left‐Handed Helical Structures with Fourteen (R)‐Chiral Centers

Abstract: The relationship between chiral centers and the helical-screw control of their peptides has already been reported, but it has yet to be elucidated in detail. A chiral four-membered ring α,α-disubstituted α-amino acid with a (R,R)-butane-2,3-diol acetal moiety at the γ-position, but no α-chiral carbon, was synthesized. X-ray crystallographic analysis unambiguously revealed that its homo-chiral heptapeptide formed right-handed (P) and left-handed (M) 3 -helical structures at a ratio of 1:1. They appeared to be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
4
1
Order By: Relevance
“…The left-handedness of the helix was exclusively controlled by the chiral centers at the side-chain β-carbons of cyclopropane. These results are in contrast to those of the uncontrolled helical screw direction of ( R , R )-Ac 4 c 3BD , ( R , R )-Ab 5,6= c, and ( R , R )-Ac 6 c 35 dBu homopeptides but are in accordance with the one-handed helical screw of ( S , S )-Ac 5 c dOM homopeptides …”
contrasting
confidence: 77%
See 1 more Smart Citation
“…The left-handedness of the helix was exclusively controlled by the chiral centers at the side-chain β-carbons of cyclopropane. These results are in contrast to those of the uncontrolled helical screw direction of ( R , R )-Ac 4 c 3BD , ( R , R )-Ab 5,6= c, and ( R , R )-Ac 6 c 35 dBu homopeptides but are in accordance with the one-handed helical screw of ( S , S )-Ac 5 c dOM homopeptides …”
contrasting
confidence: 77%
“…Homopeptides composed of a chiral five-membered ring dAA (S,S)-Ac 5 c dOM with two side chain chiral centers preferentially formed left-handed (M) helical structures without an α-chiral center. 7 Contrary to the one-handed helical structure of (S,S)-Ac 5 c dOM homopeptides, the homopeptides composed of a five,six-membered bicyclic ring dAA (R,R)-Ab 5,6= c with two side-chain chiral centers, 8 a fourmembered ring dAA (R,R)-Ac 4 c 3BD with a chiral acetal moiety, 9 or a six-membered ring dAA (R,R)-Ac 6 c 35dBu with two chiral acetal moieties 10 showed uncontrolled right-handed (P) and left-handed (M) helical-screw structures.…”
mentioning
confidence: 99%
“…The incorporation of nonproteinogenic amino acids such as α,α-disubstituted amino acids (dAAs) is one molecular strategy for creating and stabilizing helical structures. In particular, α-aminoisobutyric acid (Aib), the simplest dAA, is often utilized as a helical inducer. Peptides bearing Aib favor the formation of α- and 3 10 -helices because of the steric repulsion of the α,α-dimethyl groups. Kodama and coworkers have demonstrated the importance of Aib residues in CPPs by replacing the Aib residues of the peptide derived from trichorovin-XIIa, a class of peptaibols, with Ala residues; Ala replacement of Aib diminished the helicity of the peptide, leading to lower cell-penetrating ability.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of α,α-disubstituted α-amino acids (dAAs), such as α-aminoisobutyric acid (Aib), is a useful method for inducing and stabilizing helical conformations of peptides. It has been reported that amphiphilic cell-penetrating peptides (CPPs) containing dAAs form stable helices, which enhance peptide uptake efficiency. We have also reported that Aib-containing CPPs adopting helical conformations exhibit long-term internalization into both mammalian and plant cells with higher efficiency than conventional CPPs …”
Section: Introductionmentioning
confidence: 99%